SELEKSI DAN PEMANFAATAN ACTINOMYCETES SEBAGAI MIKROBA ANTAGONIS YANG RAMAH LINGKUNGAN TERHADAP Fusarium oxysporum f.sp. cubense SECARA IN VITRO - I MADE SUDARMA (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science))
A total of 119 different actinomycete isolate were recovered from banana crop habitats with and without Fusarium wilt disease symptom. These were than assessed for their antagonist ability against Fusarium oxysporum £sp. cubense (Foe) in vitro. Results indicated that four of all actinomycete isolate active against Foe. The four of actinomycete isolates were Streptomyces sp. l (AAo4), Streptomyces sp.2 (AAo32 ), Streptomyces sp.3 (AAo33) and Streptomyces sp. 4 (AAo35). It was can inhibit the Foe mycelium growth, 79,63%, 72,22%, 78,89% and 72,22% respectively. After tested with the 3 times replication, the four Streptomyces spp. isolate effective to control the Foe that attack Bali banana cultivars, such as Susu, Saba, Raja and Ketip.